PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUASAN KONSUMENMCDONALD’S - Maulida Layyinatus Shifaa; Eka Yuliana, Rauly Sijabat (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims first to find out the effect of brand image on McDonald's consumer satisfaction, then secondly to find out the effect of price on McDonald's consumer satisfaction, then thirdly to find out brand image and price on McDonald's consumer satisfaction. This study uses a quantitative approach. The sampling technique was carried out randomly, namely using simple random sampling, the population in this study were daily visitors who had purchased at McDonald's restaurants, the sample was selected randomly using probability sampling techniques. Field research data collection techniques include observation, interviews and questionnaires. Data analysis techniques using instrument tests, classical assumption tests, hypothesis tests, coefficient of determination tests, data from 35 respondents using IMB SPSS Version 21.0 tools. In conclusion, the test results show that brand image influences McDonald's customer satisfaction, then price influences McDonald's customer satisfaction, then brand image and price influence McDonald's customer satisfaction